Counselor Image in The Novel Ayat-Ayat Cinta 2 By Habiburrahman El Shirazy: Paul Ricoeur’s Hermeneutics Perspective - Eva Dwi Kurniawan (Jurnal Internasional Bisnis, Humaniora, Pendidikan dan Ilmu Sosial, 2021)
Literature is an imitation of human life and society. Literary works show various social phenomena and professions, such as counselors. The novel Ayat-ayat Cinta 2 by Habiburrahman El Shirazy raises the character of Fahri, who has expertise as a counselor. This study aims to seek the image of the counselor displayed by Fahri in the novel Ayat-ayat Cinta 2, abbreviated as AAC2, and discover the function of image effects in the AAC2 whole story. This present study implies a qualitative descriptive approach using Paul Ricoeur’s theory of hermeneutic analysis. The results indicate that the counselor image characterized by Fahri shows spiritual values, purity, and intelligence supported by financial power in analyzing and sorting problems. The functions of the counselor’s character seek to strengthen the theme of the novel, which is charged with Islamic da’wah values.